2020
DOI: 10.1155/2020/1820325
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Dengue Virus-Specific IgM and IgG Antibodies through Peptide Sequences of Envelope and NS1 Proteins for Serological Identification

Abstract: Dengue is an acute febrile illness caused by positive-sense single-stranded RNA virus, belonging to the family Flaviviridae and genus Flavivirus. Transmission of virus among the individuals occurred by blood-feeding Aedes mosquitoes. This virus has four serotypes differentiated on the basis of antibody neutralization assay. At present, there is no particular treatment or vaccine candidate available for dengue infection. Approximately 3.9 billion human populations are at risk of dengue virus (DENV) infection. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…In addition, another study predicted and selected common peptides among all DENV serotypes showing no similarities with other flaviviruses from the envelope and Ns1 protein regions of DENV2. Subsequently, these peptides were chemically synthesized using a solid-phase synthesis technique and evaluated by ELISA to perform DENV-specific detection of IgM and IgG from the sera of infected patients (Nagar et al, 2020). This study identified seven continuous linear peptides from the envelope region (Pep34, RCIGISNRDFVEG VSGGSWVDIVL; Pep37, NTTTASRCPTQGEP; Pep43, MENK AWLVHRQWFLDLPLPWLPGADT; Pep53, KEIAETQHG TIVIRVQYEGDG; Pep61, WFKKGSSIGQMFETTMRGA; Pep62, RMAILGDTAWDFGSLGGV; and Pep68, MNSRS TSLSVSQVLVGIVTLYLGV) and four linear peptides from the Ns1 region (Pep102, TEQYKFQPESPSKLASAIQKA; Pep111, ALNDTWKIEKASF; Pep112, PETAECPNTNRAW; and Pep115, VLESEMVIPKNFAGPKSQ).…”
Section: Envelope Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, another study predicted and selected common peptides among all DENV serotypes showing no similarities with other flaviviruses from the envelope and Ns1 protein regions of DENV2. Subsequently, these peptides were chemically synthesized using a solid-phase synthesis technique and evaluated by ELISA to perform DENV-specific detection of IgM and IgG from the sera of infected patients (Nagar et al, 2020). This study identified seven continuous linear peptides from the envelope region (Pep34, RCIGISNRDFVEG VSGGSWVDIVL; Pep37, NTTTASRCPTQGEP; Pep43, MENK AWLVHRQWFLDLPLPWLPGADT; Pep53, KEIAETQHG TIVIRVQYEGDG; Pep61, WFKKGSSIGQMFETTMRGA; Pep62, RMAILGDTAWDFGSLGGV; and Pep68, MNSRS TSLSVSQVLVGIVTLYLGV) and four linear peptides from the Ns1 region (Pep102, TEQYKFQPESPSKLASAIQKA; Pep111, ALNDTWKIEKASF; Pep112, PETAECPNTNRAW; and Pep115, VLESEMVIPKNFAGPKSQ).…”
Section: Envelope Proteinmentioning
confidence: 99%
“…Based on prediction algorithms from the DNASTAR, BCEPRED, and IEDB databases, one study selected eight potential diagnostic DENV2 peptides from the Ns1 protein that are common to all DENV serotypes (Nagar et al, 2020). These peptides were chemically synthesized, and their DENV antibody detection levels were evaluated.…”
Section: Ns1 Proteinmentioning
confidence: 99%
“…DENV serological diagnosis includes a wide spectrum of different formats and Ag designs (13), however low specificity has constantly been reported for these tests due to the presence of impurities in Ags widely used in commercial tests such as whole viral lysates. Recombinant proteins such as NS1 and Envelope proteins have helped in reducing false positivity and were rapidly adapted to different formats such as indirect ELISA, MAC-ELISA, and lateral flow devices for their commercial application (4,(14)(15)(16)(17). Nevertheless, despite the progress made with the operational characteristics and good sensitivity, challenges with false positivity remain especially with the increasing co-circulation of arthropod-borne flaviviruses across the globe (4,(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…In theory, the detection of specific antibodies (such as immunoglobulin IgG/IgM) and antigens provides a simple, rapid, reliable, and accessible strategy for the efficient and large-scale screening of suspected cases in point-of-care settings [ 1 , 2 , 3 , 4 ]. Many methods have been proposed for virus infectious disease diagnosis based on the detection of IgG/IgM antibodies [ 5 , 6 , 7 , 8 ]. Jiang et al [ 9 ] presented the label-free, real-time detection of rabbit IgG antibody over a concentration range of 0–100 μg/mL with a resolution of 0.0625 μg/mL.…”
Section: Introductionmentioning
confidence: 99%